Retinal Vessel Diameter Changes in Relation to Dark Adaptation and Acute Hyperglycemia - Per Kappelgaard; Stig K. Holfort; Oliver N. Klefter; Michael Larsen (Journal of Ophthalmology, 2018)
The purpose of this experimental clinical study was to assess the effects of dark adaptation and acute changes in glycemia on retinal vessel diameters in men. The study included 14 patients (mean age 63 years, range 48–74 years) with type 2 diabetes mellitus and minimal or no diabetic retinopathy. Retinal vessel diameters were assessed using infrared photography before and after dark adaptation, first while fasting and then at peak hyperglycemia during an oral glucose tolerance test (OGTT). Dark adaptation was accompanied by retinal vasodilatation, both during fasting (mean glycemia 7.6 ± 1.7 mM) and postprandial hyperglycemia (15.7 ± 4.2 mM). When fasting, the increase in vein diameter during dark adaptation was 2.0% after 20 min (P=0.018) and 2.9% after 40 min (P=0.010). When subjects were hyperglycemic, the increase during dark adaptation was 2.8% for retinal vein diameters (P=0.027) and 2.0% for retinal artery diameters after 20 min (P=0.002) and 1.7% for retinal artery diameters after 40 min (P=0.022). For identical conditions of light/dark adaptation, retinal vessels were dilated when subjects were fasting compared to postprandial hyperglycemia. Thus, darkness and fasting were both associated with retinal vasodilation in this short-term experiment in patients with type 2 diabetes. Future studies should determine whether both the stimuli of vasodilation lead to retinal hyperperfusion, which would support that they may be involved in the aggravation of diabetic retinopathy.